The triumph of humanity: Wiesel's struggle with the Holocaust - Willis, Robert J. (Journal of religion and health, 1991)
Confronted with the Holocaust, I pose the question: How could the human beingas a mature person survive? Through examining the writings of one survivor, Elie Wiesel, we may discover how he pictures personal humanity conquering impersonal death. By placing his reflections in an analytical psychological structure, we may illustrate responses to threat, both healthy and unhealthy responses. At the same time, we may illumine the struggle to grapple humanly with an inhuman environment. Such a discussion may encourage reflection on our own daily dealings with stressful situations; it may also serve to guide the professional assisting in the human struggle with mortality.